Effects of variable chemical reaction and variable electric conductivity on free convective heat and mass transfer flow along an inclined stretching sheet with variable heat and mass fluxes under the influence of Dufour and Soret effects - Alam, M. S. S.; Ahammad, M. U. U. (Nonlinear Analysis: Modelling and Control, 2011)
This paper deals with the effects of variable chemical reaction and variable electric conductivity on free convection and mass transfer flow of a viscous, incompressible and electrically conducting fluid over an inclined stretching sheet with variable heat and mass fluxes under the influence of Dufour and Soret effects. The non-linear boundary layer equations with boundary conditions are transferred into a system of non-linear ordinary differential equations using an established similarity transformation. These non-linear and locally-similar ordinary differential equations are solved numerically by applying Nachtsheim–Swigert shooting iteration technique with sixth-order Runge–Kutta integration scheme. Comparison with previously published work is obtained and excellent agreement is found. The effects of various parameters on the dimensionless velocity, temperature and concentration profiles as well as the local skin-friction coefficient, heat and mass transfer rate from the stretching sheet to the surrounding fluid are presented graphically and in tabulated form for a hydrogen-air mixture. The numerical results showed that chemical reaction parameter K, order of reaction n, Dufour number Df , Soret number Sr and heat (or mass) flux parameter r play a crucial role in the solutions.
Keywords: heat and mass transfer; chemical reaction; variable electric conductivity; stretching sheet; Dufour effect; Soret effect